Analisis Intensitas Kebisingan pada Area Fabrikasi PT XYZ Bintan - Effine Lourrinx; Muhammad Navis Mirza; Rizki Eka Praditya (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Noise in the industrial sector of a company caused by the use of machines and working tools to support the production process. Noise levels that exceed the threshold limit can lead to hearing loss and the risk of damage to the ears, both temporary and permanent after exposure for a certain period of time without the use of adequate protective equipment. This potential risk encourages governments in various countries to make regulations that limit the level of noise in the industry. This research was carried out by observing and measuring directly on the research object, namely by using a Sound Level Meter and repeating the data 4 times at each point of data collection on noise intensity. An analysis of the noise intensity in the PT XYZ Bintan fabrication area was carried out in order to create a working environment that is safe, comfortable and conducive and can overcome the hazards caused by the noise generated. The noise level in the PT XYZ Bintan fabrication area does not fully meet the standard noise standards in the work environment according to the Minister of Manpower Regulation Number 5 of 2018, which is 85 dBA. The results of capturing the distribution of Leq noise that have been made show that the noise level at Workshop 5 and Workshop 8 has passed the required quality standards, namely 95.1 dBA and 93.5 dBA respectively. While Workshop 9 and Workshop 10 the noise level was close to the quality standard, namely 84.3 dBA and 84.8 dBA. Mitigation efforts that have been carried out by PT XYZ Bintan are hearing protection including the use of hearing protection devices, audiometric testing as well as motivation and reduction of noise problems.